Factors influencing consumers’ attitude towards online shopping in Rangpur City - Mridha, Md. Morsalin; Hossain, Md. Sajjat; Chowdhury, Md. Salim; Al-Imran, Md.; Debnath, Dulal (International Multidisciplinary Research Journal, 2023)
Nowadays Bangladesh is called a “DIGITAL BANGLADESH”. The propensity of online shopping and businesses is increasing these days. The digital environment spreads out not only in the country but also in Rangpur City. Over the last few years, online shopping has improved and the number of people who have access to the web has increased. A positive attitude towards online shopping and selling is being observed in Bangladesh. The young generation is much more involved in space marketing or shopping than in a place. The main aim of this research is to investigate the consumers’ attitudes toward online shopping and the factors influencing consumers towards online shopping. To meet the study objectives a quantitative survey method was employed. Researchers select 150 respondents by the technique of non-probability convenience sampling. The questionnaire of the study was developed from the previous literature. The research result shows that 60% of the respondents are male, and the rest are female between the 16-59 age groups, with a Secondary school certificate to postgraduate educational level. Most of them spend 2-4 hours on the Internet daily. The result also revealed that convenience, time-saving, website design, perceived enjoyment, and people engagement and their review rating have a significant positive relationship with consumer attitudes toward online shopping.